Recognition of xyloglucan by the crystalline cellulose‐binding site of a family 3a carbohydrate‐binding module. Issue 18 (18th July 2015) - Hernandez-Gomez, Mercedes C.; Rydahl, Maja G.; Rogowski, Artur; Morland, Carl; Cartmell, Alan; Crouch, Lucy; Labourel, Aurore; Fontes, Carlos M.G.A.; Willats, William G.T.; Gilbert, Harry J.; Knox, J. Paul
Abstract : Type A non‐catalytic carbohydrate‐binding modules (CBMs), exemplified by Ct CBM3acipA, are widely believed to specifically target crystalline cellulose through entropic forces. Here we have tested the hypothesis that type A CBMs can also bind to xyloglucan (XG), a soluble β‐1, 4‐glucan containing α‐1, 6‐xylose side chains. Ct CBM3acipA bound to xyloglucan in cell walls and arrayed on solid surfaces. Xyloglucan and cellulose were shown to bind to the same planar surface on CBM3acipA . A range of type A CBMs from different families were shown to bind to xyloglucan in solution with ligand binding driven by enthalpic changes. The nature of CBM‐polysaccharide interactions is discussed. Abstract : Ct CBM3a can bind to xyloglucan in addition to crystalline cellulose. Five point mutations at the Ct CBM3a crystalline cellulose binding site abolished recognition of both crystalline cellulose and xyloglucan. XG polysaccharides, but not XG‐derived oligosaccharides, in solution can be bound by Ct CBM3a.